Electrocardiographic characteristics of distal His bundle pacing in a patient with left bundle branch block. Issue 12 (20th November 2019) - Gu, Min; Hu, Yiran; Hua, Wei; Niu, Hongxia; Zhou, Xiaohong; Zhang, Shu
Abstract: This case demonstrates the feasibility of placing the pacing lead helix at the His bundle distal to the region of left bundle branch block and reveals three types of electrocardiographic characteristics of distal His bundle pacing during correction of left bundle branch block in a patient. As the pacing lead helix was placed distal to the block, left bundle branch block correction was achieved by pacing with a low and stable capture threshold.